EVALUASI KESESUAIAN PENYIMPANAN OBAT DI SALAH SATU APOTEK KOTA CIMAHI - Elis Susilawati; ED. Yunisa M.P; Deti Siti Fatimah (Journal Syifa Sciences and Clinical Research, 2022)
Storage is one of the main factors in the maintenance of drug quality by storing properly and in accordance with standards, if it is not done will cause the quality of the drug is not guaranteed during storage in pharmacies. This study aims to find out how to store drugs and how much percentage of suitability of drug storage systems in one of Cimahi City Pharmacies Based on the Technical Instructions for Pharmaceutical Service Standards in Pharmacies in 2019. Research methods use descriptive observation and evaluation using checklist table sheets. Drug storage in one of Cimahi City Pharmacies is stored based on dosage form, therapeutic class, stability and alphabetically with a dispensing system using the FEFO system. Drug storage systems in pharmacies in accordance with the Technical Instructions of Pharmaceutical Service Standards are 86.36% while those that are not in accordance with the Technical Instructions of Pharmaceutical Service Standards which amount to 13.64% include adjacent LASA or NORUM storage, recording on less than optimal stock cards and the absence of backup electricity. The conclusion of this study shows that there are still those who are not in accordance with the Technical Instructions of Pharmaceutical Service Standards.